Potential of Bioactive Compounds In Coleus amboinicus, Lour., Leaves Against Breast Cancer By Assessment Using A Network Pharmacology Approach and Cytotoxic Test - Winarto Haryadi; Kasta Gurning; Jajah Fachiroh; Endang Astuti (Journal of Multidisciplinary Applied Natural Science, 2025)
Breast cancer is a disease that significantly contributes to global women death. The study aims to conduct in vitro activity testing and assessment with a bioinformatics approach using a pharmacological network of bioactive compounds from bangun-bangun (Coleus amboinicus) leaves extract as a breast cancer drug. The methods used are extraction of bioactive compounds by maceration and partition, identification and analysis of bioactive compounds using the Liquid Chromatography High-Resolution Mass Spectrometry (LC-HRMS) instrument, cytotoxic testing of breast cancer cells (MCF-7) and normal cells (CV-1) with the MTT method, and assessment with a bioinformatics approach through a network pharmacology. The results of the cytotoxic test of ethyl acetate extract provided better activity with IC50 value of 102.30 and 457.09 µg/mL against MCF-7 cancer cells and CV-1 normal cells. The selectivity index value of 4.23 indicates the potential for further development in the treatment of breast cancer. The results of the analysis of chemical compound content show various types of potential bioactive compounds as breast cancer anticancer; assessment of the bioinformatics approach through networks pharmacology with pathways in cancer provides predictions of signal transducer and activator of transcription 3 (STAT3) protein as the main therapeutic mechanism target in breast cancer treatment. This study provides initial information for further research on testing and utilizing bioactive compounds from C. amboinicus leaves as an alternative treatment for breast cancer.